Anatrophic Nephrolithotomy Surgery for Staghorn Calculi: A Case Report at Tertiary Care Hospital of Faisalabad, Pakistan - Tausif Ahmad, Noorshad Khan, Liaquat Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In this minimally invasive endo urological era, anatrophic nephrolithotomy is a urological procedure that is rarely performed. However, in the case of sophisticated staghorn calculus, it is still a possibility. A single sitting with a near-complete excision of the big calculus will be less expensive than numerous sittings with minimally invasive techniques. Case study: A 20 year old male patient came to Urology OPD of Pakistan Atomic Energy Commission Hospital (PAEC) from Faisalabad with diagnosis of bilateral kidney stones performed anatrophic nephrolithotomy. Results: On the fourth postoperative day, an abdominal X-ray confirmed that the right kidney was stone-free The drain was removed the same day. The ureteral stent was removed after two months. Additionally, three months following surgery, a renal ultrasound revealed no hydronephrosis and no residual stones in the right kidney. The renal function was determined to be normal. PNL is scheduled on the left side and will occur shortly. Conclusion: Open surgery anatrophic nephrolithotomy to remove Staghorn calculi is of great importance, especially in developing countries. Anatrophic nephrolithotomy thus is a valid approach for managing large Staghorn calculi with failed minimally invasive approaches.